Wprowadzenie controllingu w konglomeracie bankowo-ubezpieczeniowym. Kontekst informacyjny - Duda, Ryszard (Introduction of controlling in bank-assurance group. Information context, 2008)
Controlling introduction is connected with decentralization of management. As a result, the responsibility centres (cost and profi centres) are formed. Both controlling projecting and introducing, including responsibility centres, are multistage. The main purpose of the paper is to present the model of controlling mission of technological and organizational character. Preparing the model was assumed as a first step in project preceding connected with working on conception of controlling system of an enterprise. The purpose of controlling is to create effective and efficient management by influencing elements of management systems. It is related to strategic and operating controlling. As conclusion we can say that controlling is the concept of integrated management of the firm.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 63-70